HUBUNGAN SIKAP TENTANG PENERAPAN PROTOKOL KESEHATAN COVID-19 DENGAN STRES KERJA PADA KURIR PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) DI KABUPATEN JEMBER - Amirah Jihan Lutcfiyah Hasna; Anita Dewi Prahastuti Sujoso; Reny Indrayani (Jurnal Kesehatan Masyarakat (Undip), 2022)
The COVID-19 pandemic has caused a lot of changes in people's lives. The existence of a health policy encourages the community to help limit the spread of COVID-19, particularly among high-mobility employees such as couriers. The courier's attitude toward the COVID-19 health protocol is critical in ensuring that the implementation of COVID-19 health protocol is used to its full potential. Couriers' difficulties and challenges in completing the COVID-19 health protocol might lead to psychological problems including work stress. At PT. Tiki Lane Nugraha Ekakurir (JNE) in Jember Regency, this study will examine the relationship between attitudes toward the implementation of the COVID-19 health protocol and work stress on couriers. With a cross-sectional research design, this study takes a quantitative approach. In this study, 50 couriers from PT. Tiki Line Nugraha Ekakurir (JNE) in Jember Regency participated as respondents. The purpose was to see if there was a relationship between couriers' attitude about the implementation of COVID-19 health protocol, their age, and their length of service, and work stress at PT. Tiki Line Nugraha Ekakurir (JNE) in Jember Regency. According to the study's showed, tenure has a relationship to work stress (p-value: 0.020). Meanwhile, work stress is unrelated to age (p-value: 0.069) or attitude (p-value: 1.000).